The Effect of the Rolling Direction, Temperature, and Etching Time on the Photochemical Machining of Monel 400 Microchannels - Deepakkumar H. Patil; Sadaiah Mudigonda (Advances in Materials Science and Engineering)
The present paper describes the effect of the rolling direction on the quality of microchannels manufactured using photochemical machining (PCM) of Monel 400. Experiments were carried out to fabricate microchannels along and across the rolling direction to investigate the effect of the grain orientation on microchannel etching. The input parameters considered were channel width and rolling direction, whereas the depth of etch was the response parameters. Different channels of widths of 60, 100, 150, 200, and 250 μm were etched. The effects of the etching time and temperature of the etchant solution on the undercut and depth of the microchannels were studied. For good quality microchannels, the effects of spinning time, spinning speed, exposure time, and photoresist film strength were also taken into consideration. Optimized values of the above were used for the experimentation. The results show that the depth of etch of the microchannel increases more along the rolling direction than across the rolling direction. The channel width and depth are significantly affected by the etching time and temperature. The proposed study reports an improvement in the quality of microchannels produced using PCM.